2016
DOI: 10.1155/2016/2643470
|View full text |Cite
|
Sign up to set email alerts
|

A Hormonally Active Malignant Struma Ovarii

Abstract: Struma ovarii is a rare monodermal variant of ovarian teratoma that contains at least 50% thyroid tissue. Less than 8% of struma ovarii cases present with clinical and biochemical evidence of thyrotoxicosis due to ectopic production of thyroid hormone and only 5% undergo malignant transformation into a papillary thyroid carcinoma. Only isolated cases of hormonally active papillary thyroid carcinoma developing within a struma ovarii have been reported in the literature. We report the case of a 36-year-old woman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 16 publications
0
14
0
2
Order By: Relevance
“…Most patients with SO present no clinical symptoms and are diagnosed incidentally. In some patients, as it was in the two presented cases, they may cause symptoms similar to those typical of other ovarian tumours, such as low abdominal pain, nausea, vaginal bleeding and abnormal menstrual cycles [5,6]. Sometimes, the first symptom is palpable abdominal mass [5,7,13].…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Most patients with SO present no clinical symptoms and are diagnosed incidentally. In some patients, as it was in the two presented cases, they may cause symptoms similar to those typical of other ovarian tumours, such as low abdominal pain, nausea, vaginal bleeding and abnormal menstrual cycles [5,6]. Sometimes, the first symptom is palpable abdominal mass [5,7,13].…”
Section: Discussionmentioning
confidence: 64%
“…Struma ovarii is usually a benign tumour, being histologically and pathologically identical to normal thyroid tissue found in typical localization. Less than 5% of these tumours undergo malignant transformation [2,[6][7][8]. The age at presentation of SO is usually between 40 and 60 years [3,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…In a patient with NHL and unexplained hypertension, RNA extraction from a lymph node demonstrated increased CYP11B2 mRNA expression, confirming that hyperaldosteronism was paraneoplastic (Mulatero et al 2001). Struma ovarii is a rare subtype of ovarian cancer representing <1% of all ovarian malignancies (Lara et al 2016). It represents a monodermal teratoma composed of mature thyroid tissue; thyroid tissue must comprise more than 50 percent of the overall ovarian tissue to be classified as a struma ovarii.…”
Section: Endocrine Paraneoplastic Syndromes Secondary To the Secretiomentioning
confidence: 88%
“…The mechanism underlying the functioning status of the tumour is still unclear, but the presence of thyroid stimulating hormone receptor (TSHr) is thought to play a role. It represents the only known malignancy that secretes ectopic TSH (Lara et al 2016). Gestational trophoblastic diseases comprise hydatidiform moles, invasive moles, choriocarcinomas and placental site trophoblastic tumours.…”
Section: Endocrine Paraneoplastic Syndromes Secondary To the Secretiomentioning
confidence: 99%
“…Lara et al [11], reported a case aged 36 years old with malignant struma ovarii in 2016. They performed a left salpingoopherectomy with omentectomy.…”
Section: Discussionmentioning
confidence: 99%